Analysis The Effectiveness of Reading Park Management in Increasing Reading Interest in Bogor Regency - Syarifudin Yunus; Didik Notosudjono; Martinus Tukiran (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Community reading parks have a role in increasing reading interest. This study measures the level of effectiveness of reading park governance, with the CIPP ( Context, Input, Process, Product ) model qualitatively. The instruments used include document studies, interviews, questionnaires, observations, and focus group discussions . Data analysis is analytical in nature. interactive. It can be concluded that the level of effectiveness of the management of reading parks in increasing public interest in reading is classified as